2007
DOI: 10.4028/www.scientific.net/amr.20-21.58
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Tank Bioleaching Process for the Treatment of Complex Cu-Polymetallic Concentrates

Abstract: The focus of this paper is on the development of a bioleaching process for the treatment of complex polymetallic concentrates, containing chalcopyrite, sphalerite, galena and silver, using a moderately thermophilic culture operating around 45°C. Initial development R&D work and subsequent research for process improvements carried out in bench-scale piloting facilities will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…At present, commercial operations use acid leaching, although it is reported that alkaline heap leaching has been tested in China, and could be worth investigating for high acid consuming ores (Alta, 2011;Taylor, 2007Taylor, , 2009. Bacterial heap leaching is also being investigated for more complex, low-grade uranium ores (Gericke et al, 2008).…”
Section: Heap Leach Test Workmentioning
confidence: 99%
“…At present, commercial operations use acid leaching, although it is reported that alkaline heap leaching has been tested in China, and could be worth investigating for high acid consuming ores (Alta, 2011;Taylor, 2007Taylor, , 2009. Bacterial heap leaching is also being investigated for more complex, low-grade uranium ores (Gericke et al, 2008).…”
Section: Heap Leach Test Workmentioning
confidence: 99%
“…By continual growth of the bacteria in an environment that contains an increasing concentration of metals, the bacteria adapts and becomes tolerant to increasing toxic metals and copper. 83,84,85 Treatment of adapted cells A. ferrooxidans which are more tolerant of copper than unadapted cells by protein hydrolyzing enzymes leads to a loss of tolerance to copper. 86 …”
Section: Application Of Acidithiobacillus Ferrooxidans In Bioleachingmentioning
confidence: 99%